The Difference of Student Debris Index Chewing Apple, Pineapple and Carambola in The JKG Poltekkes Kemenkes Padang - Aljufri Aljufri; Yustina Sriani (Faculty of Public Health, Andalas University, 2017)
One deposit/layers that accumulated and are attached to the surface of the tooth is debris. Debris index can be influenced by a kind of food edible. Consumedthe food are fibrous and watery like fruits is self-cleansing. Consumefibrous fruits and contain many water like apple, pineapple and carambola can help cleaning debris on the surface of the tooth.The methodology is research sample experiment with 60 students, level I of nursing teeth (20 chewing apple, 20 chewing pineapple, 20 chewing carambola). The sample in purpose sampling from the analysis test anova one way. The results of the study the difference of debris index is apple 1,1, pineapple 1,1 and carambola 1.09. Results test one way anova value p = 0.000 it means there are a differences the decline in debris index chewing with the apple, pineapple and carambola. Conclusions is apples and pineapple better in lowering debris index than carambola. Was recomended to respondents to consume fibrous fruit and watery after eating and to daily because pure the surface of the tooth naturally.